Comparison of Three Orthoses Effects on Planter Fascitis - Ma'soumeh Nakha'ei; Mohammad Naghi Tahmasbi; Masoud Karimlou; Reza Vahab-Kashani (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Plantar Fasciitis is the common foot complaint that outbreaks as a result of an inflammation of plantar fascia. The purpose of this study was to compare the effectiveness of three orthoses, silicon heel pad, thermoplastic custom-made arch support and Tension Night splint, how they relived pain in plantar fasciitis. Materials & Methods: In this quasi experimental study that was done on 16 patients who were referred from Shariati Hospital Orthopedic ward to Saba Orthotics & Prosthetics Center age, sex, BMI, occupation and activity level were not inclusion criteria, systemic diseases and also surgery on foot in past were as exclusion criteria. The patients were assigned one by one to three treatment groups who were ready to admit them. Subject's pain was assessed for 3 months, at 2nd, 6th and 12th week, by Numerical Rating Scale and Verbal Rating Scale through phone. Data were analyzed with ANOVA, Pierson's and Spearman's correlation coefficients, Kruskal-Wallis test and Repeated Measurement test. Results: The coefficient correlation of Numerical score pain and rating score pain were 0.80. The average of morning (P=0.87), evening (P=0.198) and the worse pain (P=0.113) before entering the study were similar in three groups. The repeated measurement test defined that all the three orthoses were effective for the morning, evening and as so for the worse pain (P<0.001). There was not significant difference among the three groups in decrease of morning (P=0.483), evening (P=0.462) and worse pain (P=0.948).  Conclusion: Taking advantage of the three orthoses without any treatment was effective for the Plantar Fasciitis pain in this study.